Effect of moisture content on structural evolution characteristics of bituminous coal subjected to high-voltage electrical pulses. (1st April 2019) - Yan, Fazhi; Xu, Jiang; Lin, Baiquan; Peng, Shoujian; Zou, Quanle; Zhang, Xiangliang
Highlights: The breakdown field strength of coal decreases with the increase of moisture content. More pores and cracks will be formed during the process of electric pulse breakdown. The moisture content favors the generation of oxygen-containing functional groups. Abstract: In recent years, high-voltage electric pulse (HVEP) technology has been suggested to improve the permeability of coal seams. However, the effect of moisture content on the structure evolution of coal subjected to HVEP is not clear, which restricts the wide spread application of this technology. In this study, the breakdown voltage of coal samples with different moisture content was tested, and an exponential function relationship was established between the average breakdown field strength and the moisture content of bituminous coal samples. We investigated the changes in pore structure by combing scanning electron microscopy (SEM) and nuclear magnetic resonance (NMR) results, to better understand the pore structure evolution characteristics of coal with different moisture content. Furthermore, changes in the chemical structure of the bituminous coal samples with different moisture content subjected to HVEP were investigated by Fourier transform infrared spectroscopy (FTIR). The results show that many mesopores and macropores are formed in the coal body under the action of HVEP, and the connectivity between the mesopores and the macropores is very good. In general, the higher the moisture content of coal body, the more pores and cracks will be formed in the process of electric pulse breakdown. The total porosity of coal samples with moisture content of 1%, 1.5%, and 2% is significantly higher than that of coal samples with moisture content of 0% and 0.5% after electric pulse breakdown. Therefore, the increase of moisture content is beneficial to improve gas permeability in coal body. The FTIR spectral analysis indicates that oxidation occurs on the plasma channel surface in the breakdown process of coal samples with different moisture content. Furthermore, the increase of moisture content in coal favors the generation of more oxygen-containing functional groups, which will facilitate the desorption of methane.